A bibliometric review of trends in Indigenous tourism - Zamani, Nur Liana; Raja Yusof, Raja Nerina; Abdullah, Nawal Hanim; Ahmad, Nobaya (Human Resource Management Academic Research Society, 2023)
Indigenous tourism has become a rapidly increasing trend due to its potential to improve the marginalised economic status and political power of Indigenous people. Over the last 45 years, research on Indigenous tourism has grown rapidly. However, the review of existing Indigenous tourism study trends is limited. Thus, the purpose of this study is to furnish an overview of the evolution of scientific research on Indigenous tourism from 1977 to 2022 and to determine the direction of future research. A bibliometric approach was employed to analyse 1733 samples retrieved from the Scopus database. VOSviewer, Harzings Publish or Perish, and Microsoft Excel were utilised to analyse the data. Thereby, this study highlighted the current trends, prominent countries, institutions, and authors in Indigenous tourism. In addition, the prevalent theme and direction of further research were also discussed. This study provides a complete evaluation of the Indigenous tourism review, which could aid others in understanding Indigenous tourism development, research trends, and its institutional scientific collaboration.